2008
DOI: 10.1093/brain/awn298
|View full text |Cite
|
Sign up to set email alerts
|

Medial temporal lobe atrophy on MRI differentiates Alzheimer's disease from dementia with Lewy bodies and vascular cognitive impairment: a prospective study with pathological verification of diagnosis

Abstract: The purpose of this study was to determine the diagnostic accuracy of medial temporal lobe atrophy (MTA) on MRI for distinguishing Alzheimer's disease from other dementias in autopsy confirmed cases, and to determine pathological correlates of MTA in Alzheimer's disease, dementia with Lewy bodies (DLB) and vascular cognitive impairment (VCI). We studied 46 individuals who had both antemortem MRI and an autopsy. Subjects were clinicopathologically classified as having Alzheimer's disease (n = 11), DLB (n = 23) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
260
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(304 citation statements)
references
References 38 publications
27
260
2
3
Order By: Relevance
“…Effectively, this cerebral structure highly participates in the memory process; even more, neuropathological findings demonstrated the strong implication of typical protein depositions met in AD that occur during this medial temporal lobe atrophy (Burton, Barber et al 2009). Nevertheless, this kind of atrophy can be met in other pathologies such as FTLD or DLB, without any cerebral pathological hallmark of AD (O'Brien, Paling et al 2001;van de Pol, Hensel et al 2006).…”
Section: How Can We Deal With the Clinical Diversity Of Alzheimer's Pmentioning
confidence: 99%
“…Effectively, this cerebral structure highly participates in the memory process; even more, neuropathological findings demonstrated the strong implication of typical protein depositions met in AD that occur during this medial temporal lobe atrophy (Burton, Barber et al 2009). Nevertheless, this kind of atrophy can be met in other pathologies such as FTLD or DLB, without any cerebral pathological hallmark of AD (O'Brien, Paling et al 2001;van de Pol, Hensel et al 2006).…”
Section: How Can We Deal With the Clinical Diversity Of Alzheimer's Pmentioning
confidence: 99%
“…Atrophy in the limbic, temporal and parietal association cortices on structural MRI is a marker of neurodegeneration associated with tau neurofibrillary tangle pathology of Alzheimer's disease and DLB (Jack et al, 2004;Burton et al, 2009;Murray et al, 2013). In several studies, patients with probable DLB showed an Alzheimer's diseaselike pattern of atrophy (Whitwell et al, 2007b;Sabattoli et al, 2008;Zhong et al, 2014) while autopsy confirmation later showed that the presence of tau neurofibrillary tangles and their Braak stage (Braak and Braak, 1991) of Alzheimer's disease primarily explained the cross-sectional (Burton et al, 2009;Kantarci et al, 2012a;Murray et al, 2013) and longitudinal (Nedelska et al, 2015) atrophy observed in the medial temporal structures.…”
Section: Introductionmentioning
confidence: 99%
“…To pursue these goals, we analysed the longitudinal rates of atrophy on MRI in cortical and subcortical grey matter, with a customized atlas subdivision, which includes regions of interest involved in the pathophysiology of DLB and/or Alzheimer's disease such as basal ganglia, posterior cingulate gyrus and medial temporal lobe, temporal, occipital, parietal and frontal neocortex (Minoshima et al, 2001;Whitwell et al, 2007b;Burton et al, 2009;Teune et al, 2010;Zhong et al, 2014;McCleery et al, 2015;Nedelska et al, 2015;Mak et al, 2016). Furthermore, we investigated whether amyloid-b deposition at baseline is associated with a faster cognitive and functional decline in patients with probable DLB.…”
Section: Introductionmentioning
confidence: 99%
“…The severity of the disease, the severity of dementia and cognitive impairment, the state of higher mental functions are frequently directly dependent on the severity of atrophic changes in the brain tissue [19,[35][36][37][38]. Thus, patients with pre-clinical TDR-0 stage have 4-8% atrophy of the temporal lobes, but patients with advanced TDR-3 AD stage have 33% -62% atrophy [19,21,22,27], though vascular disorders occurring in the brain during the development of AD are at about the same level among all patients regardless of their TDR group [21,27].…”
Section: Discussionmentioning
confidence: 99%